CHEMICAL COMPOSITION OF APPROXIMATELY EQUAL MASS Hg-Mn COMPONENTS OF THE SB2 SYSTEM 46 Draconis - Tsymbal, V. V.; Kotchoukhov, O. P.; Lambert, D. L.; Khokhlova, V. L. (Одеські астрономічні публікації, 2017)
We report results of the most complete up to date elemental abundance analysis of approximately equal mass Hg-Mn components of chemically-peculiar SB2 system 46 Dra. The highdispersion S/N≥200 CCD spectrum were obtained with the echelle spectrograph of the McDonald Observatory 2.7-m reflector. Lines in the wide spectral region of 3800-9000 Å were identified and the chemical composition of each component was determined for 25 elements. Chemical anomalies of both components are found to be roughly similar: He, C, N, O and Al deficiency, nearly normal abundance of iron-peak elements, large excesses of P, Mn, Ga, Sr, Y, Zr, Ba, Pt, Au and Hg which show a common trend with atomic number. However we found significant abundance differences between the components especially for Ne, Al, S, V, Mn, Ni, Ga, Sr, Zr and Pt.